Taxidermic Signs : Reconstructing Aboriginality - Wakeham, Pauline, 1976- (Book collections on Project MUSE., 2008)
Pauline Wakeham decodes the practice of taxidermy as it was performed in North America from the late nineteenth century to the present, revealing its connection to ecological and racial discourses integral to the maintenance of colonial power. Moving beyond the literal practice of stuffing skins, Wakeham theorizes taxidermy as a sign system that conflates animality and aboriginality within colonial narratives of extinction.